Agricultural Land Use Efficiency of Latur and Nilanga Taluka of Latur District - Jadhav, Mr. O.W. (International Journal of Scientific Research and Management (IJSRM), 2017)
Today finding valuable land for agricultural is major challenge but with the help of agricultural land use efficiency level it is very easy. Other side improving the land use efficiency is chief goal of every government to increase production and productivity of region. Agricultural land use efficiency play major role in agricultural development and management. In this study an attempt has been made to find out circlewise Agricultural use efficiency. In this study Jasbir Singh’s Method of Land Use Efficiency is used to measure the land use efficiency. Latur and Nilanga Taluka of Marathwada region are chosen as study area. The regional variations in spatial pattern of land use efficiency are examined from 1993-96 to 2010-2013. The emphasis is on highlighting the basis of agriculture which influences agricultural efficiency. Agricultural efficiency is the levels of existing performance of unit at land which differentiate from one area to another. This study also helps for agricultural planning for sustainable development of this area.